SPECTROSCOPIC PROPERTIES AND JUDD-OFELT INTENSITY PARAMETERS OF Er3+ DOPED OXYCHLOROPHOSPHATE GLASSES FOR LASER APPLICATIONS - Amrouch, S.; Chalal, M.; Kermaoui, A.; Oulebsir, A.; Zaiba, S.; Zanane, H.; Djouama, T.; Abdedou, N.; Ziane, O.; Lamrous, O. (University of Eloued جامعة الوادي, 2018)
A new series of Er3+ doped oxychlorophosphate glasses (NKAZCl) with the chemical composition based on (100-x) (NaPO3-KH2PO4–Al2O3-ZnCl2), with different xEr3+molar ratio (0.5≤x≤2), were prepared by conventional melting quenching method. The spectroscopic properties of proposed glasses are investigated by applied Judd-Ofelt theories to calculate the oscillator strengths Scal, the intensity parametes (2Ω ,4Ω ,6 Ω) .The absorption and emission cross section(σabs , (λ) σem (λ) respectively, and also the optical gain cross section parameter, at 1.53μm of 4 І13/2 4 І 15/ 2 transition of Er3+ ion are calculated by using Beer-Lambert law and the McCumber theory
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Oxychlorophosphate glasses, Er3+, ZnCl2, Al2O3, spectroscopic properties, Judd- Ofelt theory